Conducting a good ward round: How do leaders do it?. Issue 3 (27th February 2022) - Merriman, Clair; Freeth, Della
Abstract: Rationale, Aims and Objectives: Ward rounds (WRs) are complex social processes. Done well, WR discussions and decisions contribute to timely, safe, effective progression of care. However, literature highlights medical dominance; marginalisation or absence of other perspectives, safety risks and suboptimal resource use. This study examined leadership behaviours and what supported good interprofessional WRs, defined as enabling interprofessional collaboration and decision making which progresses patient care in a safe and timely manner. Deepening appreciation of this art should support learning and improvements. Method: Mixed‐method appreciative inquiry (AI) into how WRs go well and could go well more often. Context: daily interprofessional consultant‐led WRs in a large adult critical care unit. Data: ethnographic and structured observations (73 h, 348 patient reviews); AI conversations and interviews (71 participants). Inductive iterative analysis shaped by Activity Theory. Participants: 256 qualified healthcare professionals working in the unit. Results: Leadership of good WRs supported (and minimized contradictions to): making good use of expertise and time, and effective communication. These three key activities required careful and skilled orchestration of contributions to each patient review, which was achieved through four distinct phases (a broadly predictable script), ensuring opportunity to contribute while maintaining focus and a productive pace. This expertise is largely tacit knowledge, learnt informally, which is difficult to analyse and articulate oneself, or explain to others. To make this easier, and thus support learning, we developed the metaphor of a conductor leading musicians. Conclusions: Whilst everyone contributes to the joint effort of delivering a good WR, WR leadership is key. It ensures effective use of time and diverse expertise, and coordinates contributions rather like a conductor working with musicians. Although WR needs and approaches vary across contexts, the key leadership activities we identified are likely to transfer to other settings.